2018
DOI: 10.1016/j.optmat.2018.02.024
|View full text |Cite
|
Sign up to set email alerts
|

The effect of excitation intensity variation and silver nanoparticle codoping on nonlinear optical properties of mixed tellurite and zinc oxide glass doped with Nd2O3 studied through ultrafast z-scan spectroscopy

Abstract: The research on Nd 3þ doped new solid-state laser hosts with specific thermo-mechanical and optical properties is very active. Nd 3þ doped tellurite glasses are suitable for these applications. They have high linear and nonlinear refraction index, wide transmittance range. The TeO 2 -ZnO (TZO) glass considered in the present work combines all those features and the nonlinear optical properties can be used for the development of Kerr-lens mode-locked sub picosecond lasers. Recently the laser performance of Nd 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 31 publications
0
6
0
3
Order By: Relevance
“…Among oxi-tellurites, TZ glasses combine good mechanical stability, chemical durability, a high linear and nonlinear refractive index, low phonon energy (wavenumber around ∼ 750 cm −1 ) when compared to silicate and borate glasses, and a wide transmission window (0.4–6 μm). TZ glasses are capable of incorporating rare-earth ions and metallic nanoparticles (NPs) with an extensive range of photonic applications [ 1 , 2 , 3 ] and are potentially suitable materials for lasers and solar cells [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among oxi-tellurites, TZ glasses combine good mechanical stability, chemical durability, a high linear and nonlinear refractive index, low phonon energy (wavenumber around ∼ 750 cm −1 ) when compared to silicate and borate glasses, and a wide transmission window (0.4–6 μm). TZ glasses are capable of incorporating rare-earth ions and metallic nanoparticles (NPs) with an extensive range of photonic applications [ 1 , 2 , 3 ] and are potentially suitable materials for lasers and solar cells [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicated that zinc tellurite bulk glasses (TeO 2 ) 100-x (ZnO) x (x = 0 to 10 wt%) form homogeneous solids and do not show phase separation [ 9 , 10 ], whereas the crystalline structure presents several polymorphous modifications in a variety of lattices in which the interatomic separation and interatomic bonding are slightly different [ 11 ]. Although the lattice polymorphisms are an intrinsic characteristic of TZ matrices, their interesting macroscopic properties have been advantageously employed as previously mentioned [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Another important application refers to the conduction and reversible memory phenomena of thin TeO 2 -ZnO-Au (TZA) films [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Os vidros formam uma importante classe de materiais hospedeiros para os íons terrasraras, particularmente para o Nd 3+ , a primeira terra-rara trivalente a ser usada em um laser de estado sólido. Comparados com os cristais, os vidros têm uma capacidade maior de absorver as terras-raras e têm maior facilidade de serem fabricados, em grandes volumes e baixo custo [1,2].…”
Section: Sumário Introduçãounclassified
“…Matrizes vítreas produzidas com óxidos de germânio e telúrio foram escolhidas devido ao alto potencial para aplicações fotônicas em função de algumas propriedades : alto índice de refração (≤ 2,0), boa resistência mecânica, durabilidade química, baixa energia de fônon (~700 cm -1 ) quando comparadas aos vidros de silicatos e boratos e larga janela de transmissão, desde a região do visível até a do infravermelho médio (400 -4500 nm) [2,7,8].…”
Section: Sumário Introduçãounclassified
See 1 more Smart Citation